Miklós Horthy Jr. and Egypt: ميكلوش هورتي الابن والمملكة المصرية - Prantner, Zoltán; Abdallah, Abdel-Ati Al-Naggar; J. Nagy, László (Études sur la Région Méditerranéenne, 2023)
There is no doubt, that Miklós Horthy Jr., the younger son of the Hungarian regent, had an indisputable role to play in boosting bilateral relations. Using his position in the Anglo- Hungarian Bank, he made six visits to Egypt, where he personally contributed to the strengthening of cooperation between the two countries. Here, we aim to portray the background, events and results of the official and unofficial visits of Miklós Horthy Jr. to Egypt, based mainly on the reports of the leading newspapers, as well as on the documents of the foreign affairs archives.